2018
DOI: 10.1186/s42358-018-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Favorable rituximab response in patients with refractory idiopathic inflammatory myopathies

Abstract: Background: Interpretation of rituximab efficacy for refractory idiopathic inflammatory myopathies (IIM) is hampered by the absence of a uniform definition of refractory myositis and clinical response. Therefore, rigorous criteria of refractoriness, together with a homogenous definition of clinical improvement, were used to evaluate rituximab one-year response.Methods: A retrospective cohort study including 43 IIM (15 antisynthetase syndrome, 16 dermatomyositis, 12 polymyositis) was conducted. All patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Most of the patients did not receive additional immunosuppressive agents during the observational period except one patient who started MTX 6 weeks after RTX administration. Our data reveals that the long-term clinical efficacy of RTX may persist, which is similar to previous studies, 45 whereas reconstitution of peripheral blood B cell lineage occurs within a few months. 46 …”
Section: Discussionsupporting
confidence: 90%
“…Most of the patients did not receive additional immunosuppressive agents during the observational period except one patient who started MTX 6 weeks after RTX administration. Our data reveals that the long-term clinical efficacy of RTX may persist, which is similar to previous studies, 45 whereas reconstitution of peripheral blood B cell lineage occurs within a few months. 46 …”
Section: Discussionsupporting
confidence: 90%
“…In the largest trial of RTX in inflammatory myositis involving 195 patients, 83% had a clinical response and the mean dose of prednisone was significantly reduced. There are no solid data on other biologicals [2, 3] . According to these data, the authors considered RTX the most appropriate treatment for this patient.…”
Section: Discussionmentioning
confidence: 99%
“…133,150,151 Increasing number of retrospective studies have shown benefit and safety of RTX in ILD associated with ASSD with reported objective improvement in PFT, ground-glass opacities and stability, or fibrosis on HRCT of chest. 100,138,139,[152][153][154][155][156][157][158][159][160] Those who had acute onset of ILD or had RTX within 12 months of disease onset had the best outcome. 139 In an open-label study of 10 patients with ASSD and refractory ILD, treatment with RTX resulted in a substantial steroid-sparing effect; clinically significant increase in FVC and/or DLCO was observed in 5 out of the 10 patients, stabilization in 4, and worsening in 1.…”
Section: Treatment In Assd: Focus On Ildmentioning
confidence: 99%